Numerical methods for solid particles in particulate flow simulations - Laure, Patrice; Beaume, Gregory; Basset, Olivier; Silva, Luisa; Coupez, Thierry (European Journal of Computational Mechanics, 2007)
The flow motion of solid particle suspensions is a fundamental issue in many problems of practical interest. The velocity field of a such system is computed by a finite element method with a multi-domain approach of two phases (namely a viscous fluid and rigid bodies), whereas the particle displacement is made by a particulate method. We focus our paper on a simple shear flow of Newtonian fluid.